Resource Base as a Guarantee of Successful of the Local Government Reform - Арабчук, Я. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article deals with the attempt of socialphilosophical analysis of the state of decentralization is carried out in Ukraine, forming of the all-sufficient incorporated territorial communities through the mechanism of territories enlargement and cardinal changes the forming principles of their budgets. The theoretical and practical assignments of adjusting of these processes and their improvement are distinguished on the basis of taking into account the corresponding suggestions and events in the field with the aim of essential improvement the grant of public services for the population. Democratic transformations that take place in Ukraine need new approaches to forming public policy of regional development and reformation of local self-government, fundamental changes in activity of local public government bodies. It requires forming and introduction of new mechanisms and instruments of this development through reformation of the budgetary system. Within the limits of regional politics the state makes the attempts of adjusting of interbudgetary relationships with the aim of accordance providing between powers and budgetary resources of local self-government. One mechanisms of such adjusting is decentralization power, perfection of administrative- territorial device, in particular, creation of capable communities by their association, creation of the real self-government based on principles of ubiquity and subsidiarity. The decentralization reform is the key reform that will allow correctly to build management system by the state and will create the terms for civil development. Key words: decentralization, mechanisms of government control, local self-government, local budgets, territorial society, regional politics, capable community, financial resources.